Carga de trabalho de enfermagem no alojamento conjunto em hospital universitário - Cabral, Beatriz Tavina Viana (2022)
In order to guarantee nursing care with scientific support and autonomy, the importance of adequate dimensioning of nursing professionals in care settings is verified. The rooming-in is a focal point of assistance to the mother and newborn binomial. It also shows that assistance in this period is extremely important to guarantee adequate care until the moment of hospital discharge. The present study has as guiding questions: which care indicators arouse a greater need for assistance in puerperal women and newborns? And what are the existing classifications for the binomial in rooming-in? The general objective is to assess the nursing workload through a specific instrument for classifying the mother-child binomial in the rooming-in unit. This is an observational, descriptive study with a quantitative approach, carried out in the rooming-in sector of a University Hospital, carried out between January and February 2022. The Instrument for the Classification of Binomial in Rooming-in proposed by Dini et al (2018), which is composed of seven care indicators, namely: Mode of delivery; Maternal morbidity and complications; Neonatal morbidity and complications; breastfeeding; Social aggravating factors; Care education and guidance and Interaction and bonding. The research was divided into three stages: the first was through the use of the instrument by Dini et al. (2018); the second refers to sociodemographic and obstetric data; and the third is from the items the Checklist for Safe Childbirth present in the medical record.Data collection took place through an active search in the rooming-in, daily, every 24 hours, in the form of an interview and document review. The research followed the ethical precepts according to Resolution No. 466/2012 of the National Health Council and was approved by the Research Ethics Committee under Certificate of Ethical Appreciation No. 54027921.7.0000.5568. Data were stored and processed using Microsoft Office Excel and Statistical Package for the Social Sciences software, version 25.0. The descriptive treatment was through means and medians, data analysis were used Student's T tests or ANOVA, Pearson's Chi-square regression model of the Generalized Estimated Equations type. A total of 213 mother-child binomials and 471 evaluations were identified, with (105; 49.3%) being vaginal/normal delivery and (108; 50.7%) cesarean delivery, with regard to delivery guidelines (124; 58.2%) received during prenatal care, while breastfeeding guidelines (131; 61.5%) received, already in the care of the newborn (124; 58.2) received. It is concluded that there was a significant difference in workload between normal and cesarean deliveries, indicating a need for targeted care for parturients who had cesarean delivery. In addition, when analyzing the indicators, it was identified that breastfeeding was responsible for the highest scores.